Local atomic structure analysis of SiC interface with oxide using chemical-state-selective X-ray absorption spectroscopy. (23rd September 2016) - Isomura, Noritake; Murai, Takaaki; Oji, Hiroshi; Nomoto, Toyokazu; Watanabe, Yukihiko; Kimoto, Yasuji
Abstract: A local atomic structure analysis of the interface between chemical vapor-deposited SiO2 and 4H-SiC was achieved via a combination of chemical-state-selective X-ray absorption spectroscopy and the use of a sample with a very thin oxide film. The Si K-edge spectrum, which monitors the SiC-assigned Auger peak, allows the SiC side of the SiO2 /SiC interface to be selectively measured through the SiO2 film. We estimate the coordination number of the first nearest neighbor to be reduced by 17% with respect to the SiC bulk. This suggests that C vacancy defects exist at the SiC side of the interface.